Pengembangan Profesionalisme Guru Melalui Peningkatan Kompetensi Profesional dan Pedagogik di Taman Kanak-kanak Pratiwi III Ladang Panjang - Desi Karmila; Delfi Eliza (Jurnal Family Education, 2022)
This study aims to determine the professional development of teachers at TK Pertiwi III Ladang Panjang through increasing professional and pedagogic competence. Furthermore, this research was conducted in TK Pertiwi III Ladang Panjang. This research methodology uses a qualitative study with a case study approach. Respondents include the head of TK Pertiwi III Ladang Panjang, along with all teachers. Based on the results of research on teacher professional development through increasing professional and pedagogic competencies, namely: First, there is an increase in pedagogic abilities, learning design abilities, students' understanding abilities, process and outcome assessment abilities, ability to carry out learning processes, and ability to develop students' potential. Second, increasing professional abilities can be described by the ability to master the field of study according to the teacher's educational background based on academic qualifications and teaching teachers according to their expertise and majors, as well as having the ability and understanding of students, the ability to master educational learning through the ability to understand the types of subjects. lessons, organize subject matter and utilize learning resources